The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jgo.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Fall-related injuries in elderly cancer patients treated with neurotoxic chemotherapy: A retrospective cohort study

Abstract: Background: Fall-related injuries are a well-described cause of morbidity and mortality in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 26 publications
(24 reference statements)
2
62
1
4
Order By: Relevance
“…19 Miscellaneous Use of diabetes medications was significantly associated with an increased risk of falling (aOR 3.2, 95% Ci 1.3-7.9) 20 The rate of fall-related injuries for patients receiving a doublet of neurotoxic chemotherapy (9.15 per 1,000 personmonths) was significantly higher than for those receiving a single neurotoxic agent (7.76 per 1,000 person-months) or a nonneurotoxic agent (5.19 per 1,000 person-months). 7 Nasal preparations (eg, treatment of asthma or allergic rhinitis) (aOR 1.49, 95% Ci 1.07-2.08) and antiglaucoma ophthalmic preparations (aOR 1.51, 95% Ci 1.10-2.09) were statistically significantly associated with an emergency department visit due to a recurrent fall.…”
Section: Digoxinmentioning
confidence: 97%
See 3 more Smart Citations
“…19 Miscellaneous Use of diabetes medications was significantly associated with an increased risk of falling (aOR 3.2, 95% Ci 1.3-7.9) 20 The rate of fall-related injuries for patients receiving a doublet of neurotoxic chemotherapy (9.15 per 1,000 personmonths) was significantly higher than for those receiving a single neurotoxic agent (7.76 per 1,000 person-months) or a nonneurotoxic agent (5.19 per 1,000 person-months). 7 Nasal preparations (eg, treatment of asthma or allergic rhinitis) (aOR 1.49, 95% Ci 1.07-2.08) and antiglaucoma ophthalmic preparations (aOR 1.51, 95% Ci 1.10-2.09) were statistically significantly associated with an emergency department visit due to a recurrent fall.…”
Section: Digoxinmentioning
confidence: 97%
“…Besides typical FRIDs such as central nervous system (CNS)-acting agents (benzodiazepines, sedatives, hypnotics, antidepressants, and antipsychotic drugs), in recent years relatively new classes (eg, anti-Alzheimer's agents, neurotoxic chemotherapeutic agents, and nasal preparations) were identified as having significant association with falls. [5][6][7] Meanwhile, results of several sporadic cohort studies showed that the degree of medication-related fall risk was dependent on one or some of the following factors: drug pharmacokinetic and pharmacodynamic (PK/PD) properties (eg, elimination half-life, metabolic pathway, genetic polymorphism, risk rating of medications despite belonging to the same therapeutic class), and/or characteristics of medication use (eg, number of medications and drug-drug interactions [DDIs], dose strength, duration of medication use and time since stopping, medication change, prescribing appropriateness, and medication adherence). However, an up-to-date review has not been Multivariate analysis of risk factors for falls in 7,908 hospitalized patients showed that benzodiazepines with very short and short half-life were positively associated with falls during hospital stays.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This occurs mainly due to their side effects; such as sedation, dizziness, postural disturbances, altered gait and balance, or impaired cognition and these drugs are usually called fall-risk-increasing drugs (FRIDs) 9 . Numerous studies have evaluated the association of medication use with the risk of falling in elderly patients [10][11][12] .…”
Section: Jfsf 93mentioning
confidence: 99%